Former Government Officials as Outside Directors: The Role of Human and Social Capital - Lester, Richard H.; Hillman, Amy; Zardkoohi, Asghar; Cannella, Albert A. (Academy of Management Journal, 2008)
The resources that individual directors bring to corporate boards are largely a function of their human and social capital. Although research has explored the value of having former federal government officials join boards, we study factors that make one particular former government official more, or less, attractive as a director than another. Specifically, we explore the depth, breadth, and deterioration of former government officials' human and social capital and find that these dimensions of human and social capital are influential predictors of corporate outside directorships.